Association between dietary patterns and sociodemographics: A cross‐sectional study of Australian nursing students. (30th August 2019) - Williams, Susan L; Vandelanotte, Corneel; Irwin, Christopher; Bellissimo, Nick; Heidke, Penny; Saluja, Sonia; Saito, Amornrat; Khalesi, Saman
Abstract: Lack of time, financial issues, and stressful clinical and educational environments in nursing studies promote higher intakes of convenience and fast foods loaded with fat and sugar, which are linked to reduced mental and physical health. In this study, we examined the dietary patterns of nursing students and their associated sociodemographic factors to inform the development of future health‐promotion interventions. A total of 548 Bachelor of Nursing students were invited to complete a survey. Associations were explored using χ 2 and logistic regression. Three dietary patterns were identified: healthy (fruit, vegetables, and legumes), Western (loaded with fat, sugar, and salt), and unbalanced. Only 21% of participants were classified as following a healthy dietary pattern, and more likely to be older (>35 years old) and have a personal annual income between AUD20 000–59 999 and 60 000–99 999. Students with one to two and three or more children were more likely to follow a Western dietary pattern. There is a need to develop interventions to improve the dietary behaviors of nursing students by health‐promoting activities and the provision of online health resources.